Navigating perceptions of risk and value : a case study on coastal adaptation planning in Aotearoa, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University, Manawatū, New Zealand - Niblock, Christine Jo-anne (Massey University, 2025)
Climate change is a wicked problem of global proportions and with broad consequences. It is exacerbating coastal hazards, such as erosion and inundation and impacting coastal communities in variable and interconnected ways. Coastal adaptation planning seeks to proactively manage these risks. Actions towards coastal adaptation reflect a multitude of value positions and ways of knowing, and these are intrinsically linked to how receptive communities are to proposed adaptation strategies. The complexities of coastal adaptation planning are highlighted, before exploring the principal components of risk-based and value-based assessment in coastal adaptation planning. The interpretation and evaluation of coastal hazard risks is particularly challenging when risk is examined in the context of the subjectivities of landscape value. Vulnerability and uncertainty add further complexities. Attributes of value can be used in risk assessment to inform coastal adaptation planning and foster local community action. For example, tolerances of risk and conceptions of what is valued and to be protected can differ greatly and be divisive across individuals, groups, and sectors. In this research, document analysis was used to explore how risk and landscape values are evaluated and how value-based risk assessment can inform coastal adaptation planning. Drawn from the literature, a Concentric Framework for Coastal Adaptation Planning was developed and applied to the Kāpiti Coast District Council’s Takutai Kāpiti Coastal Adaptation Project. As a completed coastal adaptation planning project, it presented a useful case study from which to draw insights about how planners and policymakers identified risk alongside landscape values in coastal adaptation planning. Four inter-related themes, identified from relevant literature - governance and power, risk assessment, values-based assessment and community empowerment, alongside considerations of global and local action were explored in the case study using the Concentric Framework for Coastal Adaptation Planning. This study presents a basis for exploring coastal adaptation planning in the context of local government and presents an opportunity for further research. It found that there were differences in approaches to landscape and risk assessment, from highly technical assessments of natural character, towards more nuanced assessments of social and cultural values. The complexities of planning within an evolving political landscape were also revealed in the examination of the proposed plan change, which lead to Takutai Kāpiti. It also found that, by addressing factors of vulnerability and matters of uncertainty in decision-making frameworks, planners can enhance a community’s capability to withstand, recover and adapt to coastal hazard risks. Furthermore, when values are acknowledged through meaningful participation and inclusive engagement processes, coastal adaptation outcomes are more likely to be accepted by communities. The research provides insights into the realities of coastal adaptation planning in NZ and confirms that coastal adaptation planning is a ‘wicked problem’ that can never be solved, only re-solved over and over.
Figure 1 (= Lawrence & Bell, 2024 Fig 7) is ©Crown copyright New Zealand 2024 and was therefore removed. Figure 7 (= Ministry for the Environment, 2020 Table 1 p. 9) is ©Crown copyright New Zealand 2020 and was therefore removed. Figures 10 and 17 (=MacDonald & Blazey, 2022 Fig 12 and Fig 8) are ©Jacobs New Zealand Limited 2022 and were therefore removed. Figure 22 (= Boffa Miskell, 2024 p. 58) is ©Boffa Miskell Limited 2024 and was therefore removed. Figure 2 (=Pascual et al., 2022 Fig 6 p. 36) and Figure 6 are reused under a Creative Commons Attribution 4.0 International license.
Keywords: 330407 Regulatory planning and development assessment; 410102 Ecological impacts of climate change and ecological adaptation